Proceedings of the International Congress of Mathematicians (ICM 2018) 2019
DOI: 10.1142/9789813272880_0049
|View full text |Cite
|
Sign up to set email alerts
|

ON NEGATIVE ALGEBRAIC K-GROUPS

Abstract: We sketch a proof of Weibel's conjecture on the vanishing of negative algebraic K-groups and we explain an analog of this result for continuous K-theory of nonarchimedean algebras. Negative K-groups of schemesFor a scheme X Grothendieck introduced the K-group K 0 (X) in his study of the generalized Riemann-Roch theorem Théorie des intersections et théorème de Riemann-Roch [1971, Def. IV.2.2]. In case X has an ample family of line bundles one can describe K 0 (X) as the free abelian group generated by the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Recall that in the nonsingular case, all the groups K −n (X) vanish for n > 0. See [Ker18] for some discussion about the relationship between negative K-groups and singularities in the setting of schemes.…”
Section: (I)mentioning
confidence: 99%
“…Recall that in the nonsingular case, all the groups K −n (X) vanish for n > 0. See [Ker18] for some discussion about the relationship between negative K-groups and singularities in the setting of schemes.…”
Section: (I)mentioning
confidence: 99%
“…In the general case where X ′ is an aribtrary model, we have do proceed differently. For n < 0 and α ∈ K n (X ′ on π) there exists by Raynaud-Gruson's platification par éclatement an admissible blow-up X ′′ → X ′ such that the pullback of α vanishes in K n (X ′′ on π) [Ker18,7]. In the colimit over all models this yields that K cont…”
Section: Theorem D (Theorem 610)mentioning
confidence: 99%
“…This notion was recently studied by Kerz-Saito-Tamme [KST19] and they showed that it coincides in non-positive degrees with the groups studied by Karoubi-Villamayor and Calvo. For an affinoid algebra A over a discretely valued field, Kerz proved the corresponding analytical statements to (i) and (ii); that is replacing algebraic K-theory by continuous K-theory and the polynomial ring by the ring of power series converging on a unit disc [Ker18]. Morrow showed that continuous K-theory extends to a sheaf of pro-spectra on rigid k-spaces for any discretely valued field k. The main result of this article provides analogous statements of (i)-(iii) above for continuous K-theory of rigid k-spaces; the statements (i) and (ii) extend Kerz' result to the global case and statement (iii) is entirely new.…”
Section: Introductionmentioning
confidence: 99%
“…1 This notion was recently studied by Kerz-Saito-Tamme [32] and they showed that it coincides in non-positive degrees with the groups studied by Karoubi-Villamayor and Calvo. For an affinoid algebra A over a discretely valued field, Kerz proved the corresponding analytical statements to (i) and (ii); that is replacing algebraic K-theory by continuous Ktheory and the polynomial ring by the ring of power series converging on a unit disc [28]. Morrow showed that continuous K-theory extends to a sheaf of prospectra on rigid k-spaces for any discretely valued field k. The main result of this article provides analogous statements of (i)-(iii) above for continuous K-theory of rigid k-spaces; the statements (i) and (ii) extend Kerz' result to the global case and statement (iii) is entirely new.…”
Section: Introductionmentioning
confidence: 99%
“…Our proof uses rigid analytic spaces in the sense of Tate [44] and adic spaces introduced by Huber [27]. Another approach is the one of Berkovich spaces [6] for which there is also a version of our main result as conjectured in the affinoid case by Kerz [28,Conj. 14].…”
Section: Introductionmentioning
confidence: 99%